Pupuk NPK Phoska dalam Meningkatkan Produksi Buah Pare di Kelompok Tani Sumber Rezeki, Jambi - Nasution, Hasriati; Saad, Asmadi; Yusfaneti; Mulyati, Sri (WIDA Publishing, 2024)
Bitter melon (Momordica charantia L.) possesses significant economic value and health benefits due to its content of saponins, flavonoids, polivenol, cucurbitacin glycosides, momordicin, and charantin. To achieve optimal fruit production, fulfilling essential nutrients through the application of compound fertilizers is crucial. This study aims to enhance the skills of the Sumber Rezeki Farmers Group in Desa Mendalo Indah, Kecamatan Jambi Luar Kota, Kabupaten Muaro Jambi, in cultivating bitter melon through extension services and the application of NPK Phoska fertilizer. The methods employed include providing training on NPK Phoska fertilization and conducting direct demonstrations of bitter melon planting in farmers' fields. The provided facilities include bitter melon seedlings, NPK Phoska fertilizer, agricultural tools (machetes, hoes, buckets), scales, as well as supporting materials such as teaching aids and refreshments during the fertilization demonstrations. The research results indicate that the training participants were highly enthusiastic, actively engaged in discussions, and understood how to determine the appropriate dosage of NPK Phoska fertilizer. The application of NPK Phoska fertilizer is expected to enhance the growth of bitter melon plants and produce more abundant fruits. In conclusion, the extension services and application of NPK Phoska fertilizer effectively improve the skills and productivity of the farmers group in cultivating bitter melon.